TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PENGELOLAAN ZAKAT PRODUKTIF DI LEMBAGA INISIATIF ZAKAT INDONESIA (IZI) KOTA PALU - Yusuf D; Marzuki; Ahmad Arief (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2020)
The potential for zakat if managed properly will encourage the progress and prosperity of Muslims. In practice, zakat must be given to the right person in accordance with the provisions of the Shari'a and can also be empowered productively so that it becomes a source of funds for the ummah, but generally zakat is mostly managed in a consumptive form and the management process has not been effective and efficient so that sometimes the goal of zakat has not been achieved. . The Indonesian Zakat Initiative (IZI), Central Sulawesi, shows that in its role as the Amil Zakat Institution in the city of Palu, it has tried its best in managing existing zakat. In each of its activities, the Central Sulawesi IZI is always based on regulations made by the government and makes its activities an effort to promote the welfare of the people. In the utilization of zakat funds, it is carried out with two distribution models, namely consumptive use or called charity and also a form of productive empowerment. Even so, it is undeniable that there are still shortcomings, especially in the supervision process